2008
DOI: 10.1051/forest:2008061
|View full text |Cite
|
Sign up to set email alerts
|

Colour and decay resistance and its relationships in Eperua grandiflora

Abstract: Abstract• Eperua grandiflora, which is widely distributed in the French Guiana forest region, shows high variability in decay resistance. Further information concerning this wood quality parameter is necessary, but standard testing methods are complex and time-consuming. We assessed the use of colorimetry to determine durability in heartwood samples from a range of trees.• Eperua grandiflora colour parameters were measured using a CIELAB system, revealing that the tree effect was greater than the radial positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Usually, the lightest and medium light tropical woods okoumé, sapelli, iroko and ovengol had the highest ΔE  ab values from 11.28 to 24.26. This result is in an accordance with other works dealing with the durability and colour changes of tropical woods due to biological deterioration [48,49]. However, it was simultaneously observed that after attack by C. puteana the top surfaces of wengé and padouk (darker tropical woods- Table 2) also had high In the fungal-attacked tropical woods, again no evident relationships were found between the lightness and redness (R 2 = 0.11), or the lightness and colour saturation (R 2 = 0.06).…”
Section: Colour Of Tropical Woods Exposed To the Fungus Coniophora Pusupporting
confidence: 93%
See 1 more Smart Citation
“…Usually, the lightest and medium light tropical woods okoumé, sapelli, iroko and ovengol had the highest ΔE  ab values from 11.28 to 24.26. This result is in an accordance with other works dealing with the durability and colour changes of tropical woods due to biological deterioration [48,49]. However, it was simultaneously observed that after attack by C. puteana the top surfaces of wengé and padouk (darker tropical woods- Table 2) also had high In the fungal-attacked tropical woods, again no evident relationships were found between the lightness and redness (R 2 = 0.11), or the lightness and colour saturation (R 2 = 0.06).…”
Section: Colour Of Tropical Woods Exposed To the Fungus Coniophora Pusupporting
confidence: 93%
“…On the contrary, effects of the Δa  and Δb  values of all tropical species on the ΔE  ab value were not significant ( Figures 5B, 5C). Several studies have shown that there are some relationships between the colour parameters of wood and its decay resistance [15,16,[46][47][48][49][50]. The relationship between the colour and weight loss of decayed wood is based on the type and amount of wood extractives, which have effect on the colour, and on its decay resistance.…”
Section: Colour Of Tropical Woods Exposed To the Fungus Coniophora Pumentioning
confidence: 99%
“…(1)) allowed us to determine the reference dry matter M02 (Eq. (2)) of the test specimens (Amusant et al, 2008). For each wood species, we used 12 test specimens and 12 controls per radial position (sapwood and heartwood) respectively for decay test and moisture content determination.…”
Section: Sampling Materialsmentioning
confidence: 99%
“…Figure 1a shows the variations in shape and color between heartwood and sapwood. The heartwood of eastern cedar has a dark red color that distinguishes it from the sapwood due to the higher extractives content in the heartwood (Amusant et al 2008;Freitag and Morrell 2001;Taylor et al 2002).…”
Section: Methodsmentioning
confidence: 99%